Relationship among Conflict Management Styles, Levels of Conflict and Reactions to Work in Nepalese Commercial Banks - Pandey, Kritigya (Nepalese Journal of Management, 2025)
This study examines the relationship among conflict management styles, levels of conflict, and reactions to work in Nepalese commercial banks. Employee performance is selected as the dependent variable. Similarly, avoiding styles, integrating styles, compromising styles, collaborating styles, and obliging styles are selected as the independent variables. This study is based on primary data with 141 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors affecting conflict management styles on employee performance in Nepalese commercial banks. The study showed that avoiding style has a positive impact on employee performance. It shows that the higher the avoiding style higher would be the employee performance. Similarly, integrating style has a positive impact on employee performance. It shows that the higher the integrating style higher would be the employee performance. Moreover, compromising style has a positive impact on employee performance. It shows that the higher the compromising style higher would be the employee performance. Likewise, collaborating style has a positive impact on employee performance. It shows that the higher the collaborating style higher would be the employee performance. Further, the obliging style has a positive impact on employee performance. It shows that the higher the obliging style higher would be the employee performance.